Polymorphism of Insulin-Like Growth Factor-1 (IGF-1) Gene on Bayang Ducks Using PCR-RFLP Method - T. Rafian; Y. Yurnalis (Jurnal Sain Peternakan Indonesia, 2023)
This study aims to determine the polymorphism of the IGF-1 gene in Bayang ducks using the PCR-RFLP method. This study used 120 blood samples of Bayang ducks in Kampung Binuang Dalam, Padang City, West Sumatra Province. Bayang duck blood samples were taken through the brachial vein for ± 1 mL. DNA extraction was taken from the blood using the Genomic DNA Purification Kit (Promega) Protocol. DNA was amplified using a pair of primers F: 5'- CCA GGA ATA TCT TTG GAA GCT GT-3 and R: 5'- TGC TAC GTT ACC AGC CTT GA -3 'which produced a 433 bp fragment of exon 3 IGF-1 gene, and F: 5'- CTG GAG CAG GCA GGA AAA TT - 3 'and R: 5'- TCC AGG GAC AGT GAC TCA AC -3' which produced 801 bp fragments of exon 4 IGF-1 gene. The amplification product was restricted by the DdeI enzyme, which recognized the C↓TNAG slashing site (N = G, A, T, C) for the exon three and MnII regions, which recognized the CAC↓GTG cutting site for the exon four regions. The cutting of the IGF-1 exon three gene product in Bayang ducks using DdeI as a restriction enzyme only recognized the C↓TNAG cutting site. The cutting results visualized with 2% agarose gel showed two genotypes: homozygous (+ / +) of 41 samples and the heterozygote (+/-) genotype of 60 samples. The cutting of the IGF-1 exon four gene product in Shadow ducks using MnII as a restriction enzyme only recognized the CAC↓GTG cutting site. The cutting results visualized with 2% agarose gel showed three types of genotypes, namely four samples homozygous (+/+), 67 samples heterozygous (+/-), and 49 samples homozygous (-/-). Based on the results of the study, it can be concluded that the IGF-1 gene in Bayang ducks is polymorphic, with the frequency of the IGF-1|DdeI genotype being in a hardy-weinberg imbalance, and the IGF-1|MnII genotype in a hardy-weinberg equilibrium.